THE EFFECT OF LMS-SUPPORTED BLENDED LEARNING ON STUDENTS' ENGLISH PROFICENCY IN ENGLISH FOR ACADEMIC PURPOSE INSTRUCTION - Rahman, Faisal; Azhimia, Faida; Aisyah, Noor (Journal of English Educational Study (JEES), 2025)
This research aims to identify the effect of Learning Management System (LMS) supported blended learning on students’ English proficiency in English for Academic Purpose (EAP) classroom. Previous studies have explored the broader benefits of blended learning. However, there is a lack of studies specifically investigating its impact on EAP instruction. This study aims to address this gap by providing a comprehensive analysis of LMS-supported blended learning in EAP, contributing to a deeper understanding of its potential benefits and challenges in this specialized area of language education. This research implies quasi experimental study method with one group pretest posttest experimental design. The population of this research was 138 students of pharmacy study program of Sari Mulia University academic year 2023/2024 who took EAP course divided into three classes. The sample of this research was 45 of class A students who were selected using cluster random sampling technique. The result found that LMS supported blended learning has no significant effect on students’ English mastery in EAP classroom. This indicates that main hypothesis (H1) is rejected and alternative hypothesis (H0) is accepted. Nevertheless, LMS supported blended learning is still helpful and applicable in EAP instruction since the students’ mean score indicates small improvement on their English proficiency.